(untitled) (Marketing Journal, 2025)
This article explores the development stages of digital services in Uzbekistan, focusing on their socio -economic and legal foundations. Particular emphasis is placed on the formation of digital infrastructure, the implementation of electronic signature systems, the automation of public services, and the results of the "Digital Government Project Management Center." Based on legal frameworks and statistical data, the study analyzes the process of service digitalization and its positive outcomes. The article also highlights the strategic advantages of digital transformation through indicators such as financial stability, public trust, and growth in value added. 519